Pengaruh Social Media Marketing terhadap Keputusan Pembelian Sepeda Motor Merek Yamaha (Studi Kasus pada PT. Alfa Scorpii Meulaboh) - Ramadhani, Wanda; Muzakir, Muzakir; Jalil, Ivon (Universitas Teuku Umar, 2024)
This research aims to ascertain how Social Media Marketing (SMM) effects consumers decisions to buy Yamaha brand motorbikes at PT. Alfa Scorpii Meulaboh, West Aceh. The participants in this study are consumers of PT. Alfa Scorpii Meulaboh, West Aceh from August to October 2023. To find the sample size using random sampling techniques and selecting samples calculated with the Slovin formula. This study uses employs a quantitative methodology, collecting data through the distribution of questionnaires. In this case, researchers used simple linear regression analysis to find out the results, namely 60.37% of variable Y was explained by variable Alfa Scorpii Meulaboh, West Aceh.